Thomas Cromwell the untold story of Henry VIII's most faithful servant - Borman, Tracy (New York Atlantic Monthly Press, 2014)
As Henry VIII's right-hand man, Cromwell was the architect of the English Reformation, secured Henry's divorce from Catherine of Aragon and plotted the downfall of Anne Boleyn, and upon his arrest, was accused of trying to usurp the King himself. Borman reveals a different side of one of the most notorious figures in history: that of a caring husband and father, a fiercely loyal servant and friend, and a revolutionary who helped make medieval England into a modern state. His seismic political, religious, and social reforms had an impact that can still be felt today. This is the true story of a controversial and enigmatic man who forever changed the shape of his country.
Includes bibliographical references (pages 403-440) and index.
Keywords: Cromwell, Thomas, Earl of Essex, 1485?-1540.